Analisis Yuridis Pada Dampak Program Transmigrasi Nasional Terhadap Kemajuan Sosial Ekonomi - Monica Sandra Ferenanda; Aknes Galih Sumirat; Sulis Tyaningsih; Febrilia Rustina Arfiani; Muhamad Rois Nova Rona (Jurnal Relasi Publik, 2023)
The problem of population density is still problematic for the government because of the unequal distribution of the population and social and economic conditions that have not changed. Then the government created a transmigration program that could be used for socio-economic change and progress that could be felt by the community later. Transmigration is a government policy that exists in Indonesia with the aim of distributing the population evenly in various regions, especially outside Java. The problem in this research is the legal regulations related to the transmigration program and the impact of transmigration on socio-economic progress. The type of research used is descriptive qualitative where the reference sources are based on books and literature studies. After conducting research, researchers came to the conclusion that the problem of population density can be overcome with this transmigration program, then the impact that can be felt from transmigration is one of the community's economy which is now starting to improve.